Construction planning, equipment, and methods - Peurifoy, Robert L.; Schexnayder, Clifford J.;Ledbetter, William B. (London, United Kingdom : McGraw Hill Education, 1996)
A guide to construction planning, equipment and methods. The text covers topics such as: equipment cost; tractors and related equipment; compaction and soil stabilization; compressed air; blasting rock; pumping equipment; concrete; and asphalt.
The planning process for equipment and methods; equipment cost; engineering fundamentals of moving earth; tractors and related equipment; scrapers; excavating equipment; cranes; trucks and wagons; compaction and soil stabilization; belt conveyors; compressed air; drilling rock and earth; blasting rock; pile and pile driving equipment; pumping equipment; production of crushed stone; concrete; asphalt. Appendices: Interest tables; SI units.
Includes index.
Keywords: BUILDING CONSTRUCTION AND MATERIALS